Bilateral Breast Reconstruction With Profunda Artery Perforator Flaps and Immediate Implant Augmentation. Issue 1 (14th January 2020) - Chu, Carrie K; DeFazio, Michael; Largo, Rene D; Ross, Merrick
Abstract: The smaller volume of the profunda artery perforator (PAP) flap relative to that of abdominal flaps limits the size of breast reconstruction that may be achieved. Immediate implant augmentation of abdominal free flaps has been performed, but immediate implant augmentation of PAP flaps has never been described. A 54-year-old woman with BRCA2 mutation, submuscular implants, and previous abdominoplasty presented for nipple-sparing mastectomies (NSM). Autologous tissue volume was inadequate to support reconstruction to the desired size. She wished to avoid serial expansion. Skin quality was unsuitable for direct-to-implant reconstruction. The patient underwent bilateral NSM. The previous implants were removed with capsule preservation. Bilateral PAP flaps were harvested and anastomosed to the internal mammary vessels. Moderate classic profile 170-mL smooth round silicone implants were placed into the existing capsule pockets with lateral capsulorraphy. There were no flap, implant, or infectious complications. Initial mastectomy skin and nipple ischemia completely resolved without necrosis. Donor site healing was uneventful. At 8 months, the reconstruction is supple and the implants remain well-positioned without rippling. One minor revision was performed for fat grafting and to correct lateral nipple deviation. PAP flap breast reconstruction with immediate implant augmentation is technically feasible. Advantages include improved prosthetic coverage, allowing for immediate reconstruction to a larger size with reduced concern regarding mastectomy skin necrosis and threat to the device, optimal implant camouflage, and improved substrate for secondary fat grafting if necessary. Level of Evidence: 5